The legend of Korra : patterns in time - Konietzko, Bryan; DiMartino, Michael Dante; Silverstein, Rachel; Delliquanti, Blue; Xu, Jen; Rhodes, K. (Konietzko, Bryan. Legend of Korra., 2022)
"Join Korra, Asami, Mako, Bolin, Tenzin, and more familiar faces from The Legend of Korra, featured in stories specially crafted by a bevy of talented comics creators!"--